Redox potential in human semen: Validation and qualification of the MiOXsys assay. (30th December 2020) - Vassiliou, Anna; Martin, Catherine H.; Homa, Sheryl T.; Stone, Jesse; Dawkins, Andrew; Genkova, Mariya N.; Skyla Dela Roca, Helen; Parikh, Sejal; Patel, Jinal; Yap, Tet; Killeen, Aideen P.
Abstract: Seminal oxidative stress (OS) is a major contributing factor to male infertility. Semen analysis cannot identify reactive oxygen species (ROS), which can be measured using a chemiluminescence assay. Measurement of redox potential provides a more comprehensive assessment of OS, although the test has yet to be fully validated. This study aimed to validate the MiOX sys analyser for measuring static oxidation–reduction potential (sORP). Results demonstrated that duplicate measurements must be taken, sensors must be batch tested, and sockets should be regularly changed to avoid inconsistency in measurement. Measurement of sORP using MiOX sys exhibited good reproducibility across different operators ( p = 0.469), analysers ( p = 0.963) and days ( p = 0.942). It is not affected by mechanical agitation ( p = 0.522) or snap freezing and thawing ( p = 0.823). The stability of sORP over time requires further verification, particularly in samples with high initial sORP. Measurement is temperature sensitive between 2 and 37°C, significantly increasing with increasing temperature ( p = 0.0004). MiOX sys is a more stable assay for assessing OS than chemiluminescence methods and permits greater flexibility for sample handling. MiOX sys could be implemented to complement semen analysis as part of routine diagnostic testing for male infertility and may be useful in identifying contributing factors to idiopathic infertility.